The Contested Crown Repatriation Politics between Europe and Mexico - Carroll, Khadija von Zinnenburg (University of Chicago Press, 2022)
Following conflicting desires for an Aztec crown, this book explores the possibilities of repatriation. In The Contested Crown, Khadija von Zinnenburg Carroll meditates on the case of a spectacular feather headdress believed to have belonged to Montezuma, the last emperor of the Aztecs. This crown has long been the center of political and cultural power struggles, and it is one of the most contested museum claims between Europe and the Americas. Taken to Europe during the conquest of Mexico, it was placed at Ambras Castle, the Habsburg residence of the author's ancestors, and is now in Vienna's Welt Museum. Mexico has long requested to have it back, but the Welt Museum uses science to insist it is too fragile to travel. Both the biography of a cultural object and a history of collecting and colonizing, this book offers an artist's perspective on the creative potentials of repatriation. Carroll compares Holocaust and colonial ethical claims, and she considers relationships between indigenous people, international law and the museums that amass global treasures, the significance of copies, and how conservation science shapes collections. Illustrated with diagrams and rare archival material, this book brings together global history, European history, and material culture around this fascinating object and the debates about repatriation.